Factors associated with stroke formation in blunt cerebrovascular injury: An EAST multicenter study. Issue 2 (2nd February 2022) - Esposito, Emily C.; Kufera, Joseph A.; Wolff, Timothy W.; Spalding, M. Chance; Simpson, Joshua; Dunn, Julie A.; Zier, Linda; Burruss, Sigrid; Kim, Paul; Jacobson, Lewis E.; Williams, Jamie; Nahmias, Jeffry; et al.
Abstract : BACKGROUND: Stroke risk factors after blunt cerebrovascular injury (BCVI) are ill-defined. We hypothesized that factors associated with stroke for BCVI would include medical therapy (i.e., Aspirin), radiographic features, and protocolization of care. METHODS: An Eastern Association for the Surgery of Trauma–sponsored, 16-center, prospective, observational trial was undertaken. Stroke risk factors were analyzed individually for vertebral artery (VA) and internal carotid artery (ICA) BCVI. Blunt cerebrovascular injuries were graded on the standard 1 to 5 scale. Data were from the initial hospitalization only. RESULTS: Seven hundred seventy-seven BCVIs were included. Stroke rate was 8.9% for all BCVIs, with an 11.7% rate of stroke for ICA BCVI and a 6.7% rate for VA BCVI. Use of a management protocol ( p = 0.01), management by the trauma service ( p = 0.04), antiplatelet therapy over the hospital stay ( p < 0.001), and Aspirin therapy specifically over the hospital stay ( p < 0.001) were more common in ICA BCVI without stroke compared with those with stroke. Antiplatelet therapy over the hospital stay ( p < 0.001) and Aspirin therapy over the hospital stay ( p < 0.001) were more common in VA BCVI without stroke than with stroke. Percentage luminal stenosis was higher in both ICA BCVI ( p = 0.002) and VA BCVI ( p < 0.001) with stroke. Decrease in percentage luminal stenosis ( p < 0.001), resolution of intraluminal thrombus ( p = 0.003), and new intraluminal thrombus ( p = 0.001) were more common in ICA BCVI with stroke than without, while resolution of intraluminal thrombus ( p = 0.03) and new intraluminal thrombus ( p = 0.01) were more common in VA BCVI with stroke than without. CONCLUSION: Protocol-driven management by the trauma service, antiplatelet therapy (specifically Aspirin), and lower percentage luminal stenosis were associated with lower stroke rates, while resolution and development of intraluminal thrombus were associated with higher stroke rates. Further research will be needed to incorporate these risk factors into lesion specific BCVI management. LEVEL OF EVIDENCE: Prognostic and Epidemiologic, Level IV. Abstract :